Positive results on discreteness and openness for mappings of finite distortion. Issue 12 (1st December 2016) - Villamor, Enrique
Abstract : In this paper, we prove some positive results on discreteness and openness of mappings of finite distortion under some integrability condition on the distortion and the multiplicity function of the mapping. We also show that in some sense, our results are sharp.